2016
DOI: 10.3389/fphy.2016.00035
|View full text |Cite
|
Sign up to set email alerts
|

Sensing in the Mouth: A Model for Filiform Papillae as Strain Amplifiers

Abstract: Texture perception of foods is a common yet remarkably unstudied biophysical problem. Motivated by recent experiments reporting the presence of corpuscular endings in tongue filiform papillae, we develop in this work a mechanical model of the human tongue covered with filiform papillae in the form of elastic beams. Considering the typical flows that occur in the mouth during oral evaluation of Newtonian liquids, we suggest that filiform papillae may act either as direct strain sensors and/or as indirect strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…Such high aspect ratios make them ideal candidates for mechanosensing via fluid-structure interactions with liquids entering the oral cavity. Recently, theoretical investigations of isolated filiform papillae-like posts in the presence of viscous flows suggested that local deflections of a single papilla could generate stresses relevant for sensory input [14]. Such a mechanism for sensing stresses, while not yet causally shown, is hinted at in new observations in mice [15] which indicate that filiform papillae are co-located with nerve endings expressing Piezo2, a mechanosensitive ion channel whose involvement in touch mammalian cells has been evidenced recently [16].…”
Section: Introductionmentioning
confidence: 99%
“…Such high aspect ratios make them ideal candidates for mechanosensing via fluid-structure interactions with liquids entering the oral cavity. Recently, theoretical investigations of isolated filiform papillae-like posts in the presence of viscous flows suggested that local deflections of a single papilla could generate stresses relevant for sensory input [14]. Such a mechanism for sensing stresses, while not yet causally shown, is hinted at in new observations in mice [15] which indicate that filiform papillae are co-located with nerve endings expressing Piezo2, a mechanosensitive ion channel whose involvement in touch mammalian cells has been evidenced recently [16].…”
Section: Introductionmentioning
confidence: 99%
“…Our simulated stimulus concentrations match both types of experiments quite well and can explain the significant temporal difference between them. This is the key improvement of our approach over previous tongue surface models 3,17,25 , where the tongue surface is traditionally modeled as a compartment that the fluid movement can convectively transport stimuli to the interface between tongue and liquid but can't penetrate through the interface. In our diffusion-dominant sip-and-hold simulations, we already assumed that the interface is at saturated concentration and that the convective transport in the fluid zone is 100% efficient, but the simulation results still fall significantly short of Kelling and Halpern's results.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior region of human tongue has mainly two types of papillae, fungiform and filiform, with the latter of greater density. As summarized in Table 1, we chose various distribution densities and diameters to cover the range of values reported in the literature 17,19,21,25 .…”
Section: Porous Media Properties Of the Human Tongue Surface: Permeabmentioning
confidence: 99%
See 2 more Smart Citations